Design of an order management website and automatic queue number system to improve service efficiency in MSMEs Bakso Mas Anto Marelan - Wardani, Aisyah; Abdul Khaliq; Hanna Willa Dhany (Cattleya Darmaya Fortuna, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector require fast, organized, and efficient services to improve customer satisfaction. Bakso Mas Anto Marelan is one of the MSMEs that still manages orders and queues manually, which often causes problems such as unorganized queues, order recording errors, and service delays. This study aims to design a website for order management and an automatic queue number system to improve service efficiency at Bakso Mas Anto Marelan. The research method includes needs analysis, system design, implementation, and application testing. The designed website allows operators to manage order data, monitor order status, and automatically generate queue numbers. The automatic queue number system helps arrange customer service order fairly and transparently. The results of this study indicate that the implementation of an order management website and an automatic queue number system can accelerate service processes, reduce recording errors, and improve queue management. Therefore, the designed website is expected to be an effective solution to enhance service efficiency in MSMEs, particularly at Bakso Mas Anto Marelan.